Answer:
A.) 2x - 9x - 30 = -6
Step-by-step explanation:
hello !
to solve this system of equations, first, we substitute the equation to the <em>y </em>variable in the equation . Therefore, we get:
now, we simplify by multiplying -3 to the variables inside the parenthesis, which, in short, is also called the distributive property. thus, we get:
Answer:
D) b =
Step-by-step explanation:
First, move all the terms that do not include b to the left side with S:
S = 2ab + 2bc + 2ac
S - 2ac = 2ab + 2bc
Now, factor out 2b from the right side:
S - 2ac = 2b(a + c)
Divide both sides by 2(a + c):
b =
Finally, multiply out the denominator:
b =
Answer:
5/8
Step-by-step explanation:
well we 1 14/8 so lets turn that to a whole number which is 12/8 (you multiply the denominator by 1 and add the 4)
12/8 - 7/8 = 5/8 ( since both denominators are the same numbers you can simply subtract the numerator )
Answer: Population
Step-by-step explanation:
-13m = -377
m= -377/-13
m=29
the negatives cancel out. so just do 377/13 which equals 29